Analysis of factors related to respiratory disorders complaints of scavengers At Klotok Landfill Kediri City - Prasetyo, Anastasya Ferronica Putri; Endah Wahyuningsih, Nur; Suhartono, Suhartono (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2023)
Klotok landfill is a place where the waste is collected by the community every day. Klotok landfill was also used as a source of livelihood for scavengers. Scavengers working in landfills are prone to respiratory problems due to dust and pollutant gases produced through the waste decomposition process. The purpose of this study was to analyze the factors that have a relationship with scavengers' respiratory complaints at the Klotok landfill. This study used an analytic observational research design with a cross-sectional approach. The research was conducted on 43 scavengers with the total sampling technique used. Data was collected through interviews using questionnaires and observation in the TPA environment. The results showed that 67.4% of scavengers at the Klotok TPA experienced respiratory disorder complaints. The study also revealed a relationship between the use of masks (p=0.003), years of service (p=0.027) and age (p=0.002) with scavengers' complaints of respiratory disorders. And there was no relationship between smoking habits (p=0.826), working hours (p=0.191), and gender (p=1.000) with scavengers' complaints of respiratory disorders.